Astragalus glycyphyllos L.: antiviral activity and tablet dosage formulation of a standardized dry extract - Aleksandar Shkondrov; Anton Hinkov; Venelin Cvetkov; Kalina Shishkova; Daniel Todorov; Stoyan Shishkov; Ivan Stambolov; Krassimira Yoncheva; Ilina Krasteva (Biotechnology & Biotechnological Equipment)
Astragalus glycyphyllos L. is widely used in Bulgarian folk medicine. Extracts from this plant have antiproliferative, antitumor and immune stimulating effects in vitro and in vivo. The aim of this study was to examine the potential antiviral activity of a standardized extract from the aerial parts of the plant and to formulate it in a suitable dosage form. A dry extract was obtained, and its phytochemical composition was determined by ultra-high-performance liquid chromatography–high resolution electrospray ionization mass spectrometry (UHPLC-HRESIMS). The extract contained flavonoids and predominantly saponins. 17(R),20(R)-3β,6α,16β-trihydroxycycloartanyl-23-carboxylic acid 16-lactone 3-O-β-D-glucopyranoside was used as a reference for quantitation. The extract had 3% saponins. The antiviral activity of the extract was tested against Simplexvirus humanalpha type 1 (acyclovir sensitive) and 2 (acyclovir resistant) in vitro. Between 60% and 70% of protection was reached against both virus strains when the extract (at the maximal non-toxic concentration of 0.6 mg/mL) was added simultaneously with and 1 h after Madine and Darby bovine kidney cell inoculation. The extract was also tested in combination with acyclovir only against Simplexvirus humanalpha type 1, in vitro. Further, the lyophilized extract was mixed with appropriate excipients aiming to prepare tablets via direct compaction. The optimized tablets fulfilled the requirements of the pharmacopoeia for disintegration and friability. Thus, the study demonstrated the possibility to formulate a standardized extract of A. glycyphyllos in tablets and their potential for adjuvant antiviral application in further trials.